Travel Distance and Regional Access to Cardiac Valve Surgery - Hawkins, Robert B. (J Card Surg, 2019)
OBJECTIVE: Evidence in other surgical subspecialties suggests patients traveling farther to undergo surgery have worse outcomes. We sought to determine the impact of travel distance and travel beyond closest center on outcomes after valve surgery. METHODS: Patients who underwent valve surgery ± CABG with a Society of Thoracic Surgeons (STS) predicted risk and zip code were extracted from a statewide STS database (2011–2016). Patients were stratified by those receiving care ≥ 20 miles from the closest surgical center (Traveler) or at the closest center (Non-Traveler). Multivariate logistic regression assessed the effects of travel distance and traveler status on mortality and major morbidity adjusted for STS predicted risk, median income by zip code, and payer status. RESULTS: Median travel distance for all patients (n=4,765) was 19 miles and after risk-adjustment increasing distance was associated with reduced operative mortality (OR 0.94 [0.89–1.00], p=0.049) with no impact on major morbidity. Travelers (445 patients, 9.3%) had lower median income, higher self-pay and re-operative status, but similar urgent/emergent status and STS risk as Non-Travelers. Travelers had lower operative mortality (1.6% vs 4.3%, p=0.005) which remained statistically lower after risk-adjustment (OR 0.32 [0.14–0.75], p=0.009). This mortality difference was particularly pronounced in patients with postoperative complications (3.1% vs 7.9%, p=0.005). CONCLUSIONS: Contrary to other surgical subspecialties, farther travel distance and bypassing the nearest surgical center were associated with lower rates of operative mortality and failure to rescue. Either referral patterns or financials reasons may result in Travelers ending up at high performing centers that prevent escalation of complications.